Snake Toxins Labeled by Green Fluorescent Protein or Its Synthetic Chromophore are New Probes for Nicotinic acetylcholine Receptors - Kasheverov, Igor E.; Kuzmenkov, Alexey I.; Kudryavtsev, Denis S.; Chudetskiy, Ivan S.; Shelukhina, Irina V.; Barykin, Evgeny P.; Ivanov, Igor A.; Siniavin, Andrei E.; Ziganshin, Rustam H.; Baranov, Mikhail S.; Tsetlin, Victor I.; Vassilevski, Alexander A.; et al. (Frontiers in Molecular Biosciences, 2021)
Fluorescence can be exploited to monitor intermolecular interactions in real time and at a resolution up to a single molecule. It is a method of choice to study ligand-receptor interactions. However, at least one of the interacting molecules should possess good fluorescence characteristics, which can be achieved by the introduction of a fluorescent label. Gene constructs with green fluorescent protein (GFP) are widely used to follow the expression of the respective fusion proteins and monitor their function. Recently, a small synthetic analogue of GFP chromophore (p-HOBDI-BF2) was successfully used for tagging DNA molecules, so we decided to test its applicability as a potential fluorescent label for proteins and peptides. This was done on α-cobratoxin (α-CbTx), a three-finger protein used as a molecular marker of muscle-type, neuronal α7 and α9/α10 nicotinic acetylcholine receptors (nAChRs), as well as on azemiopsin, a linear peptide neurotoxin selectively inhibiting muscle-type nAChRs. An activated N-hydroxysuccinimide ester of p-HOBDI-BF2 was prepared and utilized for toxin labeling. For comparison we used a recombinant α-CbTx fused with a full-length GFP prepared by expression of a chimeric gene. The structure of modified toxins was confirmed by mass spectrometry and their activity was characterized by competition with iodinated α-bungarotoxin in radioligand assay with respective receptor preparations, as well as by thermophoresis. With the tested protein and peptide neurotoxins, introduction of the synthetic GFP chromophore induced considerably lower decrease in their affinity for the receptors as compared with full-length GFP attachment. The obtained fluorescent derivatives were used for nAChR visualization in tissue slices and cell cultures.